Organogels as modern drug carriers - Sowa-Kasprzak, K.; Żwawiak, J.; Zaprutko, L. (Polimery, 2021)
The paper is a literature review concerning the uses of substances in the form of organogels. Thanks to their unique properties, susceptibility to external factors and specific structure, organogels form a kind of storage tanks for medicinal substances and are used as carriers in controlled release of active substances to specific sites in the human body. The formation process, physicochemical properties and classification system of organogels as well as most important substances which form organogels used as drug carriers, were described.